13‐1: Invited Paper: White Quantum Dot Light‐Emitting Diodes With Improved Efficiency and Color Stability. Issue 1 (2nd June 2017) - Lee, Changhee; Jung, Heeyoung; Lee, Yeonkyung; Bae, Wan Ki
Abstract : We demonstrate efficient, color‐stable, white quantum dot based light‐emitting diodes (WQLEDs). Based on a systematic study on electrical properties of charge injection and transport layers, we can significantly improve electron‐hole balance injected into the QD emissive layer within QLEDs. Our WQLEDs exhibit color‐stable white‐light‐emission over varying operation conditions up to the maximum brightness over 35, 000 cd/m 2 .